The Extract of Purple Sweet Potato Against Heat-Shock Protein 70 Expression in White Male Rat of Atherosclerosis Model - Meddy Setiawan; Fitriana Yulanda (Majalah Obat Tradisional, 2021)
Shock protein 70 (Hsp-70) molecule is pro-inflammatory mediator cytokine that trigger atherosclerosis. The purple sweet potato has many natural antioxidants such as flavonoids (anthocyanins) and is valuable for reducing Hsp-70 expression due to its antioxidant content.This study aims to determine the effect of purple sweet potato (Ipoema batatas L.) extract in reducing the Hsp-70 levels in the white male rat atherosclerosis model.This study was a posttest-only control group design with normality, homogeneity, ANOVA, post hoc test, correlation, and regression tests. There were five groups in this study. Groups 1 (negative control) and 2 (positive control) were given 2 ml/day of high-cholesterol diet for eight weeks, and the other three groups were given purple sweet potato extract at 24, 48, and 96 mg/kg doses weight per day for eight weeks. Results: The purple sweet potato extract affected the Hsp-70 levels in Wistar strain rats (p < 0.05). There was a significant difference in the Hsp-70 level between the positive control group and the group with purple sweet potato extract. The highest Hsp-70 level reduction was seen in the group with a 96 mg/day dose of purple sweet potato extract. In conclusion, theadministration of purple sweet potato extract (I. batatas L.) reduced the Hsp-70 levels. The dose of 96 mg/kg BW/day had the highest effect on decreasing Hsp-70 levels in the male rat atherosclerosis model.